Palatabilizantes em dietas de leitões recém-desmamados - Martinez, J.f.; Amorim, A.b.; Faria, D.e.; Nakagi, V.s; Sartori, M.m.p.; Marques, M.f. (Universidade Federal de Minas Gerais, Escola de Veterinária, 2014)
In order to verify the effectiveness of sugar and sweeteners containing saccharin and neohesperidin in diets of piglets, two experiments were conducted, both with 42 newborn piglets weaned at 21 days old. Were offered three diets: control diet (DC), diet with sugar (DA) and diet with sweetener (DE). The experiments were done in randomized blocks, the first of which had seven replicates and two animals per experimental unit and the second, six replicates and one animal per experimental unit comprising a factorial 3 x 2 + 1 design (three diets, two slaughter ages: at 28 and 35 days of age and slaughter on the day of weaning). In the first experiment, the animals remained in the nursery facilities until 63 days of age to evaluate the performance and the economic viability of the diets. In the second experiment, the animals were slaughtered to weigh the organs, measure the length of the small intestine and collect segments of the duodenum and jejunum to determine intestinal morphology. There were no differences between diets for the average dairy feed intake (ADFI), average dairy gain (ADG) and gain:feed (G:F) in Periods 1 (21 to 28 days), 3 (21 to 50 days) and 4 (21 to 63 days old). In Period 2 (21 to 35 days), animals that consumed DE had higher (P<0.05) ADFI and ADG, compared to those fed the DA. In Periods 1, 2 and 3 a lower cost per kg of the diet of live weight gain and better economic indicators for the animals fed DE were observed. No differences were observed between the diets when evaluating intestinal morphology and organ weights, except for the weight of the stomach, which was higher in animals fed DE. The inclusion of sweetener is effective in improving performance in Period 2, and is viable under the economical point of view.

Com o intuito de verificar a eficácia do açúcar e do edulcorante à base de sacarina sódica e neoesperidina nas dietas de leitões, foram realizados dois experimentos, ambos com 42 leitões recém-desmamados aos 21 dias de idade. Foram oferecidas três dietas: dieta controle (DC), dieta com açúcar (DA) e dieta com edulcorante (DE). Os experimentos foram em blocos ao acaso, sendo o primeiro com sete repetições e dois animais por unidade experimental e o segundo com seis repetições, um animal por unidade experimental, e arranjo fatorial 3 x 2 + 1 (três dietas, duas épocas de abate: aos 28 e 35 dias de idade e um abate no dia do desmame). No primeiro experimento, os animais permaneceram nas instalações de creche até 63 dias de idade para avaliação do desempenho e da viabilidade econômica das dietas. No segundo experimento, os animais foram abatidos para se proceder à pesagem de órgãos, medição do comprimento do intestino delgado e coleta dos segmentos do duodeno e jejuno para realização da morfometria intestinal. Não houve diferenças entre as dietas para consumo diário de ração (CDR), ganho diário de peso (GDP) e conversão alimentar (CA) nos períodos 1 (21 aos 28 dias), 3 (21 aos 50 dias) e 4 (21 aos 63 dias de idade). No período 2 (21 aos 35 dias), os animais que consumiram a DE apresentaram maior (P<0,05) CDR e GDP, se comparados aos que consumiram a DA. Nos períodos 1, 2 e 3, foi observado menor custo da dieta por kg de peso vivo ganho e melhores índices econômico e de custo para os animais que consumiram DE. Ao se avaliar a morfometria intestinal e o peso de órgãos, não se observou diferença entre as dietas, com exceção para o peso do estômago, que foi maior nos animais que consumiram DE. A inclusão de edulcorante é eficaz em melhorar o desempenho no período 2, além de ser viável sob o ponto de vista econômico.
Flavors in diets for weanling pigs
Keywords: pig; intestinal morphology; performance; sugar; sweetener; suíno; açúcar; desempenho; edulcorante; morfologia intestinal